USING RESTATE, ANSWER, PROVE, SUM UP (RAPS) TECHNIQUE TO IMPROVE DESCRIPTIVE TEXT WRITING SKILL - titin sholichah (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2019)
Writing is one of the four language skills that is viewed as the most difficult skill to be mastered. The seventh graders of MTs Negeri 2 Kota Magelang in the school year 2018/2019 are ones of those who face some difficulties in writing descriptive text. RAPS is offered as a technique to improve their learning motivation and skill in writing descriptive text. The objectives of this research are to know whether the use of RAPS technique can improve the learning motivation of writing descriptive text of the seventh graders of MTs Negeri 2 Kota Magelang in the school year 2018/2019 and to know how great the improvement of descriptive text writing skill of the seventh graders of MTs Negeri 2 Kota Magelang in the school year 2018/2019 after the implementation of RAPS technique. The writer did the research through three phases; they are Pre- Cycle, Cycle 1, and Cycle 2. The data of this research are collected from the students’ written test, questionnaire, observation, and documentation. All the data are analyzed using both qualitative and quantitative data analysis technique. The result of research shows that RAPS technique give great improvement on the students’ learning motivation and skill in writing descriptive text.